Superhydrophobic diamond-coated Si nanowires for application of anti-biofouling'. (1st July 2020) - Long, Wenjing; Li, Haining; Yang, Bing; Huang, Nan; Liu, Lusheng; Gai, Zhigang; Jiang, Xin
Abstract: The effect of the surface wettability of plasma-modified vertical Si nanowire array on the bio-fouling performance has been investigated. The Si nanowires prepared by a metal-assisted chemical etching technique exhibit a super-hydrophilic surface. The treatment in CH4 /H2 gas plasma environment leads to the decoration of graphite and diamond nanoparticles around Si nanowires. The detailed interface between graphite/diamond and Si nanowire was characterized by HRTEM technique. These surface-modified nanowire samples show an increased water contact angle with ultrananocrystalline diamond decorated ones being superhydrophobic. The immersion test in chlorella solution reveals that the diamond-coated Si nanowires possess the least attachment of chlorella in comparison with other Si nanowires. This result confirms that the coating of Si nanowires with diamond nanoparticles shows the best behavior in anti-biofouling. Importantly, this work provides a method fabricated super-hydrophobic surface for the application of biofouling prevention.